Pemanfaatan Limbah Pertanian dan Peternakan Sebagai Pupuk Kompos Alternatif Ramah Lingkungan untuk Pertanian Berkelanjutan - Lalla, Milawati; Sudiarta, I Made; Laboko, Asriani I (Jurnal Likhitaprajna, 2024)
Anorganic fertilizers that are used continuously for a long time will result in land degradation and farmers’ dependence on the use of anorganic fertilizers. For the reason, needs to be accompanied by the organic fertilizer in form of compost. Compost row materials are easy to obtain because they come from agricultural and livestock waste whitch has not been utilized optimally. Making compost from agricultural and livestock waste must continue to be developed by providing training. The aim of activity is to increase participants’ knowledge and skills in making organic fertilizer so that they can reduce the use of anorganic fertilizer. The activity was carried out in the form of a demonstration on how to make compost fertilizer. The organic materials use are goat dung, cow dung, swallow dung, banana weevil, pineapple peel, Chromolaena leaves, Gliricidia leaves, rice straw, EM4, brown sugar and water. The activity begins with preparing tools and materials, weighing the ingredients, mixing ant storing them in container for fermentation. As a result of this activity is that participants understand how to make compost fertilizer, the materials that can be used and produce compost products.